The effect of Hepatitis D co-infection on the immunologic and molecular profile of Hepatitis B in asymptomatic Chronic Hepatitis B patients in southwest Nigeria (2020)
Introduction: Hepatitis D infection causes severe form of viral hepatitis in humans and only affects those with hepatitis B either as a co-infection or superinfection. The aim of this study was to determine the prevalence of Hepatitis D and its effect on the immunologic and molecular profile of Hepatitis B among asymptomatic Chronic Hepatitis B patients in Abeokuta. Methodology: A cross-sectional study of 99 chronic HBV patient who met the inclusion criteria. All the patients were tested for HBsAg, anti HCV, HDV antigen, anti HDV, HBsAg quantification, and HBV DNA quantification. Associations were tested for and P value less than 0.05 was considered significant. Results: The participants included 53 (58%) male and 38 (42%) females with ages ranging from 18 to 69 (means 39 ± 11) years. Ten (11%) participants were positive for HDV-Ag while 1 (1.1%) was positive for anti-HDV. Five (5.5%) were positive for HIV 1 &2 while 1 (1.1%) was positive for anti HCV. HBV DNA quantification ranged from 15 to 17,000,000 IU/ml while HBsAg quantification ranged from 0.25 to45,520 IU/ml. There was no statistically significant relationship between HDV-Ag and age (p = .51), sex (p = .73), HBV DNA (p = .8) and HBsAg quantification (p = 1). Conclusion: The prevalence of HDV-Ag among asymptomatic treatment naïve chronic hepatitis B patients in Abeokuta was 11% and there was no significant difference in the levels of HBV DNA and HBsAg among those with or without hepatitis D.